Eclessiastical Law, the Indigenous Council of the Hospital of Cuzco, and links between Murúa and Guaman Poma - Cárdenas Bunsen, José (2020)
This essay examines the use of ecclesiastical council records in the works of Martin de Murua and Guaman Poma de Ayala. It argues that Murua used the Council decrees to support his authority as chroniclerand to present his work as an extension of the Council’s. This would have allowed him to oﬀer advice about Indian matters to civil and ecclesiastical authorities. In a similar direction, Guaman Poma used the decrees of the Lima Council meetings in several chapters of his chronicle to sustain his main proposals for ecclesiastical reform. The main diﬀerence between his use of these documents and that of Murua’s is that Guaman Pomaused them to demolish the friar’s image, show the inefcacy of his potential advice to Church ofcials, unauthorize his books and suggest the punishments Murua deserved because he desobeyed and manipulated ecclesiastical jurisdiction.